Relationships as Resistance: Transformative Adult Learning for Sustainability in the Climate/Environmental Justice Movement - Cameron, Sheena (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2026)
At the core of the climate calamity is a clash in beliefs, values, knowledge, and actions affecting relationships between humans and the natural world. Although there is an urgent need for systems change, there is also a need to radically reimagine white settler knowledge systems and relationships that are responsible for the climate crisis. This article aims to move the conversation about sustainability and adult learning toward shifts in white settler paradigms and relationships. By sharing findings about transformative adult learning from a qualitative research study that focuses on collaborations between Mi’kmaw, Wolastoqewiyik, and white settler participants in the climate/environmental justice movement in what is colonially known as New Brunswick, Nova Scotia, and Prince Edward Island, this article argues that real climate action hinges on confronting the worldviews of white supremacy, colonialism, and capitalism. This article highlights the transformative adult learning that has happened through relationships from these movement struggles, and that has affected how participants have shifted their understanding of and actions toward sustainability for climate/environmental justice.